Konsep Dan Isu Had Kifayah, Kemiskinan Bandar Dan Jantina Dalam Pengagihan Zakat - Ahmad Fahme Mohd Ali; Mohd Faisol Ibrahim; Muhammad Ridhwan Ab. Aziz; Fuadah Johari (Labuan Faculty Of International Finance, UMSKAL, 2024)
Volume: 8 (page: 14–26)